Association of homeobox B13 (HOXB13) gene variants with prostate cancer risk in an Iranian population - Roudi, Raheleh (Med J Islam Repub Iran, 2018)
Background: Prostate cancer is a complex condition in which both genetic and environmental factors concomitantly contribute to the tumor initiation and progression. Recently, HOXB13 has been proposed as a susceptibility gene for prostate cancer. Objective: The present study was conducted to determine the existence of potential variations in HOXB13 gene in Iranian men with prostate cancer (PCa) compared to benign prostatic hyperplasia (BPH) cases. Methods: HOXB13 genetic status was screened in 51 samples, including 21 blood and tissue of PCa cases, and compared to 30 cases affected by BPH using PCR/sequencing. Then, the existence of potential association was investigated between genomic DNA alterations in blood and tissue PCa specimens. Results: Analysis of BPH tissues showed single nucleotide variations c.366C > T (rs) or c.513T > C (rs9900627) in exon 1, but not in exon 2. Evaluation of PCa tissues revealed 2 cases with both synonymous c.366C > T and c.513T > C variants and 2 cases with the synonymous c.366C > T variant in exon 1. The variants c.366C > T and c.513T > C, simultaneously or separately, were found in blood samples of PCa patients. The novel variant c.127A > G in exon 2 was detected in 1 PCa blood sample. Our analysis indicated a significant reciprocal correlation between HOXB13 mutation in the tissue and blood samples of PCa cases (p= 0.02). Conclusion: The variants in exon 2 of HOXB13 may influence the risk of prostate cancer. Also, evaluation of HOXB13 mutation may be considered as a novel marker for screening PCa. Further investigations are warranted to evaluate the clinical significance of HOXB13 in Iranian population.